Examination of Elder Abuse and Death Anxiety in Older Adults With a Chronic Disease - Karaman, Seda; Turan, Gulcan Bahcecioglu; Yilmaz, Merve Cayir; Karabulutlu, Elanur Yilmaz (Wiley, 2025)
AimThis study was conducted to examine elder abuse and death anxiety in older adults who had chronic diseases. DesignThe present study is a cross-sectional and correlational study. MethodsThis study was conducted with 200 patients who met the research criteria and agreed to participate in the study and who were admitted to the internal medicine outpatient clinics of a university hospital in Elazig, eastern Turkey. Data were collected by using 'Descriptive Information Form' Hwalek-Sengstock Elderly Abuse Screening Test (H-S/EAST) 'Death Anxiety Scale (DAS)'. ResultsThe mean DAS score of 8.66 +/- 2.87 was evaluated as high and the mean H-S/EAST score of 6.41 +/- 3.78 was evaluated as moderate risk of abuse. It was found that the independent variable H-S/EAST total score affected DAS total score positively (beta = 0.633) and explained 38% (p < 0.001). Among the variables included in the model, gender, age and employment status were found to be positive (beta = 0.243, beta = 0.222, beta = 0.222) statistically significant predictors of H-S/EAST total score. In addition, it was found that gender was a positive (beta = 0.318) and statistically significant predictor of DAS total score (p < 0.05). ConclusionsOlder individuals with chronic illness have a moderate risk of abuse and a high level of death anxiety. As the risk of elder abuse increases, death anxiety also increases. In addition, gender is an important predictor of elder abuse and death anxiety. In line with these results, it is recommended to identify groups with high potential for abuse, to organise awareness-raising training programs to prevent abuse and to conduct evaluations for abuse and death anxiety at regular intervals. Also, the results of this research will contribute to nursing literature and will be useful for future interventional research. Public ContributionThere is no public contribution.
Keywords: chronic disease; death anxiety; elder abuse; nurse; older adult; patient